Assessing Matrimonial Real Property Law on First Nation Reserves: Domestic Violence, Access to Justice, and Indigenous Women ... - Darling, Elysa (Law, 2019)
This thesis offers a doctrinal analysis and assessment of the Family Homes on Reserves and Matrimonial Interests or Rights Act (FHRMIRA) and the case law and legislative history that led to its enactment. FHRMIRA operates on First Nation reserves with respect to matrimonial real property and includes provisions dealing with the division of property upon relationship breakdown or death of a spouse and protections from domestic violence, like emergency protection and exclusive occupation orders. This thesis assesses the utility of FHRMIRA with respect to the protection it provides to Indigenous women experiencing domestic violence, as well as their access to justice in this context. In addition, it examines the challenges First Nations experience enacting their own matrimonial real property laws, whether under FHRMIRA or other legal frameworks. It also includes a review of First Nations matrimonial real property laws enacted pursuant to FHRMIRA and the extent to which they protect against domestic violence. ...